2021
DOI: 10.46827/ejefr.v4i4.1033
|View full text |Cite
|
Sign up to set email alerts
|

Structural Flexibility and Corporate Responsiveness in the Business Environment: A Theoretical Review

Abstract: The diverse nature of modern business operations and environment has made it a strategic necessity for organization to have a proper understanding of the spontaneous activities in their business environment. It was based on this notion that this study theoretically reviewed literature on the role of structural flexibility on corporate responsiveness to business environment, x-rayed the three basic measures of corporate responsiveness. Consequently, the study found that structural flexibility plays inestimable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 23 publications
(31 reference statements)
0
6
0
Order By: Relevance
“…A prior study has reported that SF plays an important role in organizational performance because it is an actionable and manifest organizational approach in the market [40]. Further, SF facilitates the firm's ability to maneuver its capacity and exhibit market-driving behaviors that promote its ability to stay ahead of its competitors by being the first to develop innovative products and services [29].…”
Section: Structural Flexibilitymentioning
confidence: 99%
See 3 more Smart Citations
“…A prior study has reported that SF plays an important role in organizational performance because it is an actionable and manifest organizational approach in the market [40]. Further, SF facilitates the firm's ability to maneuver its capacity and exhibit market-driving behaviors that promote its ability to stay ahead of its competitors by being the first to develop innovative products and services [29].…”
Section: Structural Flexibilitymentioning
confidence: 99%
“…Structural flexibility (SF) denotes the managerial abilities or competencies necessary to adapt a firm's strategy to changes in the external business environment [29]. When a firm is structurally flexible, its management can adjust the roles, responsibilities, and working processes of its employees to meet the changing needs of the business [39].…”
Section: Structural Flexibilitymentioning
confidence: 99%
See 2 more Smart Citations
“…Significantly, structural flexibility plays an incalculable role in facilitating corporate functions. Organizations enjoy favorable market positions due to changes in their structure ( Georgewill, 2021 ). Therefore, firms should focus on reconfiguring structural flexibilities to increase their responsiveness.…”
Section: Literature Reviewmentioning
confidence: 99%